Acute pneumonia: infection or inflammation in the lung? - Klepikov, I. (Journal of Respiratory Diseases, 2019)
This commentary examines pneumonia as infection and inflammatory syndrome, parsing diagnostic criteria and implications for antimicrobial stewardship.